A quantitative analysis of the evolution of the US wage distribution, 1970 - 2000 - Guvenen, Fatih 1973-; Kuruşçu, Burhanettin 1974- (National Bureau of Economic Research, 2007)
In this paper, we construct a parsimonious overlapping generations model of human capital accumulation, and study its quantitative implications for the evolution of the U.S. wage distribution from 1970 to 2000. One of the key features of the model is that individuals differ in their ability to accumulate human capital, which is the main source of wage inequality in this model. We examine the response of this model to skill-biased technical change (SBTC), which is modeled as an increase in the trend growth rate of the price of human capital starting in early 1970's. Due to the heterogeneity in ability and age, the responses of different individuals to SBTC are systematically different from each other, generating rich behavior in the evolution of relative wages. We consider different scenarios regarding how individuals' expectations evolve during SBTC. Specifically, we study the case where individuals immediately realize the advent of SBTC (perfect foresight); and the case where they initially underestimate the future growth of the price of human capital (pessimistic priors), but learn the truth in a Bayesian fashion over time. Lack of perfect foresight appears to have little effect on the main results of the paper. The model is quantitatively consistent with several trends including the rise in overall wage inequality; the fall and rise in the college premium; the rise in within-group inequality; the stagnation in median wage growth, and the small rise in consumption inequality despite the large rise in wage inequality. Overall, the model shows promise for explaining disparate trends in the evolution of the wage distribution in a unifying human capital framework.